Perancangan Sistem Informasi Penjualan Sepeda Motor Berbasis Web pada Showroom Arios Jaya Motor - Sitepu, Fernanda Jekita F.; Siringoriongo, Rimbun; Perangin-angin, Resianta (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2024)
The Arios Jaya Motor showroom sales system currently still uses manual systems and methods, making the sales process take a long time and is inefficient. Currently, online sales systems are widely used in various showrooms, even individual companies such as Live Monza are given the opportunity to run their business. At the "Arios Jaya Motor" motorbike exhibition, there were obstacles in the sales process so that it was difficult to organize information on goods, sales, the media used in sales still used leaflets or brochures which were not evenly distributed and had a wide reach. to reach , and also many social media consumers have difficulty finding the latest information or learning about the latest things. Determining system requirements is carried out through data collection methods using observation, interview and library research techniques. This research will create an information system that allows the "Arios Jaya Motor" showroom to expand sales, units and display first reports and provide services to consumers.